Novel use of MgO nanoparticle additive for enhancing the thermal conductivity of CuO/water nanofluid - Nfawa, Sadeq R.; Abu Talib, Abd Rahim; Basri, Adi Azriff; Masuri, Siti Ujila (Elsevier, 2021)
The present work aims to address the low thermal conductivity of CuO/water nanofluid due to the spherical shape of CuO nanoparticles by adding small amount of magnesium oxide (MgO) nanoparticles to the nanofluid. Novel CuO–MgO/water hybrid nanofluid has been synthesised and studied at different volume concentrations (0.125–1.25%) of 80% CuO and 20% MgO nanoparticles suspended in water at different range of temperatures from 25 to 50 °C on its thermal conductivity. The study demonstrated that increasing volume concentration of nanoparticles has enhanced the thermal conductivity, but drops slightly when the volume concentrations are above 1%. Furthermore, the results showed that the effect of temperature on thermal conductivity enhancement is similar to the effect of volume concentration, especially at higher temperatures. The highest enhancement of thermal conductivity of 16% was achieved at volume concentration of 1.25% and temperature of 50 °C. Furthermore, sensitivity analysis showed that the optimum condition to prepare the CuO–MgO/water hybrid nanofluid could be used in industrial applications at volume concentration of 0.75% and temperature of 50 °C. Finally, the study proposed an empirical correlation to measure the thermal conductivity of CuO–MgO/water hybrid nanofluid based on data experiments results.